Welfare states, real income and poverty - Lane Kenworthy (Luxembourg Income Study (LIS), 2004)
Welfare state supporters typically contend that social-welfare programs boost the incomes of low-earning households. Critics argue that, over time, such programs reduce the growth of economic output and/or employment. As a result, redistribution may produce stagnant or even declining real incomes for those at the bottom. A number of recent cross-country empirical studies have found that welfare state generosity is strongly associated with low relative poverty, but there has been virtually no cross-national analysis of welfare state effects on absolute poverty, which is at the heart of the critics' argument. I use Luxembourg Income Study (LIS) data to examine the relationship between welfare state generosity and absolute poverty for working-age households in Sweden, Germany, the United Kingdom, Canada, and the United States from the mid-1970s to 2000. Consistent with the critics' charge, the countries with the most generous welfare states experienced rising pretax-pretransfer absolute poverty. Yet the actual causal significance of welfare state generosity in this development is questionable. On the whole, the comparative evidence seems more consistent with the view of welfare state supporters. Germany, with its relatively generous social-welfare programs, had the lowest levels of both pretax-pretransfer and posttax-posttransfer absolute poverty throughout the period. And the sharpest decline in posttax-posttransfer absolute poverty, as well as the second lowest level as of 2000, were found in Sweden, the country with by far the most generous welfare state.
Keywords: 330; Sozialstaat; Einkommenseffekt; Niedrigeinkommen; Armut; Öffentliche Sozialleistungen; Schweden; Großbritannien; USA; Deutschland; Kanada